Obtaining and studying properties of biodestructable composite films based on polyethylene - IH Turdikulov; BN Mamadiyorov; MQ Saidmuhammedova; AA Atakhanov (Open Journal of Chemistry - Peertechz Publications, 2020)
At present, polyolefins are a heavily produced thermoplastic, and they are used in different industries. Approximately one-third of produced plastics are used in the packing industry, and this volume will only be increased in the future. The advantages of plastic packaging , such as strength, flexibility, moisture stability, comfort, safety and low cost, are accompanied by a disadvantage: they do not decompose in natural conditions, which causes considerable ecological problems, namely, plastic waste composes half of the domestic rubbish.